An in-ear pulse wave velocity measurement system using heart sounds as time reference - Roman Kusche and Paula Klimach and Ankit Malhotra and Steffen Kaufmann and Martin Ryschka (Current directions in biomedical engineering, 2015)
Pulse wave measurements provide vital information in medical diagnosis. For this reason, a measurement system is developed for determining the transient time of the pulse wave between the heart and the ear. To detect pressure variations in the sealed ear canal, caused by the arriving pulse wave, an in-ear sensor is developed which uses heart sounds as time reference. Furthermore, for extracting the heart sounds from the pressure measurements and calculating the pulse wave transient time, a MATLAB-based algorithm is described. An embedded microcontroller based measurement board is presented, which realizes an interface between the sensor and the computer for signal processing.
Keywords: Heart Sounds; In-Ear Sensor; Patient Monitoring; Pre-Ejection Period (PEP); Pulse Transient Time (PTT); Pulse Wave Velocity (PWV)